1994
DOI: 10.1177/107110079401501105
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary Screw Fixation of Lateral Malleolus Fractures

Abstract: A biomechanical evaluation of intramedullary versus buttress plate and lag screw fixation of lateral malleolus fractures is combined with a clinical evaluation of 44 patients with lateral malleolus fractures who underwent intramedullary screw fixation. The biomechanical study was performed in experimentally produced, Weber B, supination-eversion ankle fractures. The fractures were fixed with one of the two above fixation methods and then placed under a torsional load to failure. Sixteen cadaver ankles were tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 14 publications
0
32
1
Order By: Relevance
“…While limited fixation is biomechanically weaker than lateral or postero-lateral plate osteosynthesis [3,25], the absence of any loss of fracture reduction in the present series suggests that while not absolutely rigid, fracture fixation is clearly stable. We have found no evidence to suggest that this less rigid fixation compromises fracture healing or clinical outcome.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…While limited fixation is biomechanically weaker than lateral or postero-lateral plate osteosynthesis [3,25], the absence of any loss of fracture reduction in the present series suggests that while not absolutely rigid, fracture fixation is clearly stable. We have found no evidence to suggest that this less rigid fixation compromises fracture healing or clinical outcome.…”
Section: Discussioncontrasting
confidence: 46%
“…In tandem with the move towards less invasive surgical approaches in other areas of orthopaedic surgery, there have been a number of studies in the literature examining the results of operatively treated fibular fractures using alternative techniques, such as cerclage wiring supplemented with lag screws, intra-medullary and bio-absorbable fixation [2,3,7]. The rationale for adopting these more conservative approaches has been to respect the integrity of an often already compromised soft tissue envelope and hence to minimise the "second hit" of surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Bankston, et al [16] they found the Intramedullary screw provided 66.5% of the strength of native bone compared to the lateral buttress plate provided 61.5%. This was not statistically significant, but it did prove that an Intramedullary screw provides stable fixation, thereby assuring that rehabilitation can be instituted early without the risk of loss of reduction.…”
Section: Discussionmentioning
confidence: 99%
“…The long intramedullary screw also allows better purchase within the fibular canal than a smooth pin (while accommodating the distal fibular lateral bow), therefore eliminating hardware migration [5]. Furthermore, Bankston et al demonstrated biomechanically that this particular fixation device was superior in strength, although not statistically followed up compared to other fixations with plate and screws [16]. They reported their clinical results using open reduction and internal fixation of lateral malleolus fractures with an intramedullary screw, which demonstrated stable fracture fixation (allowing early weight bearing) and a 100% rate of union in their series.…”
Section: Introductionmentioning
confidence: 99%
“…O ut of the various modalities of treatment option for fracture of lateral malleolus, [1][2][3][4][5][6][7][8] open reduction and internal fixation (ORIF) is the most preferred option for restoration of the anatomic ankle mortise with reduction of talar shift and correction of fibular length and rotation. Direct lateral approach has been most commonly used for the ORIF of lateral malleolar fractures.…”
mentioning
confidence: 99%